Ranking Regime and the Future of Vernacular Scholarship - Mayumi Ishikawa (Arizona State University, 2014)
World university rankings and their global popularity present a number of far-reaching impacts for vernacular scholarship. This article employs a multidimensional approach to analyze the ranking regime's threat to local scholarship and knowledge construction through a study of Japanese research universities. First, local conditions that have led to the perpetuation of the world university rankings are examined. Next, the use of bibliometric indicators in performance assessment, a critical consequence of the popularization of the world university rankings, is tested against two prevailing factors in Japanese academia: the bipolar character of academic publishing and institution-centered audit. Despite high-flying idealism, the quest to improve positions in the rankings may fall short of addressing real needs of enhancing individual performance in pursuit of globally relevant research and ensuring equity among different generations of scholars. The study also points to the precarious future of vernacular scholarship, as the rankings celebrate audit culture and export its norms as well as an increasingly inward-looking propensity of Anglo-American academic circles to the rest of the world.